Empowering Community Leadership and Learning for Immigrant Right: A Cultural-Historical Activity Theory Investigation of an Urban Korean American Community Organization - Junghwan Kim (Adult Education Research Conference, 2012)
This study aims to understand how a Korean American community organization‘s activists engage in learning throughout their daily activities for community leadership. For this purpose, the study uses cultural-historical activity theory as a theoretical framework and critical ethnography as a research method. I identified a community leadership network that includes three activities for community leadership and contradictions in the network as (possible) obstructions and potential driving forces for community leadership and learning. By resolving contradictions, expansive learning including individual transformation occurs. Based on the findings, conclusions and implications are discussed. Keywords: Learning in the community, Community Leadership, Community organization, Cultural-historical activity theory
Keywords: Learning in the community; Community Leadership; Community organization; Cultural-historical activity theory